Effect of transcutaneous electrical nerve stimulation on hemodynamic variables: systematic review and meta-analysis - Ívina Alves Chaves, Lenara; Magalhães de Almeida Ramos, Nayara; Cipriano Junior, Gerson; Alves da Silva, Weder; Valdez Lima, Francisco; Pereira da Silva, Maria Eduarda; Arruda Teixeira, Matheus; R. Chiappa, Gaspar (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: Transcutaneous electrical nerve stimulation (TENS) uses different combinations of frequency (low or high), excitation threshold (motor or sensory), and site of application (local or ganglion). The aim of the present study was to investigate the acute effect of TENS on hemodynamic variables in different populations and to determine whether differences exist between low-frequency (< 10 Hz) and high-frequency (≥ 10 Hz) TENS, between motor and sensory excitability thresholds, and between local or ganglionic application. Methods: The Cochrane, EMBASE, SCOPUS, CINAHL, and PUBMED databases were searched for randomized clinical trials in which TENS was administered noninvasively with surface electrodes in the adult population (subjects aged 18 years or older). Results: Thirteen articles met eligibility criteria and included a total of 371 subjects. The outcomes were the effects of TENS on blood flow, peripheral vascular resistance, heart rate, systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean blood pressure (MBP). A moderate increase in blood flow was noted when high frequencies were applied at the sensory threshold and above the ganglion. A decrease in peripheral vascular resistance was noted when TENS was administered at the sensory threshold above the ganglion. Significant changes in MBP and DBP were noted when high frequencies were administered at the sensory threshold and a significant difference in MBP was noted when TENS was administered locally. Conclusion: The results show that TENS is able to modify hemodynamic responses. Moreover, it is important to determine the frequency, excitability threshold and site of application to achieve the expected results.